'Most of the time, I am the three-tiered support system' - subject teachers' views on tiered support and part-time special education in lower secondary schools - Kotilainen, Ninnu; Takala, Marjatta (European journal of special needs education, 2025)
This study examines subject teachers' views on support for learning in mainstream lower secondary schools in Finland. Because Finnish legislation on support for learning changed in 2010, we wanted to explore subject teachers' views on how support is being delivered in practice. Our data consist of 115 subject teachers' answers to an electronic questionnaire and were examined using content analysis, complemented with frequencies. The results indicate a need for better resources and for structures that support teacher collaboration in lower secondary schools. Open communication and clearer definitions of subject teachers' and special education teachers' (SETs') roles are also required. According to subject teachers, the most important aspect of SET work is part-time special education, meaning that SETs provide individual support for students. The support system needs to be defined in greater detail to work effectively. However, subject teachers' attitudes seem inclusive.